Outcomes of Extra-Octave Fractures in children - Colton Ryan; William Hennrikus (Annals of Musculoskeletal Medicine - Peertechz Publications, 2019)
Background: There are limited studies differentiating between the two main treatment options for Extra-Octave fractures. The purpose of the present study is to report the outcomes when treating the Extra-Octave fracture in children. Methods: 12 small fi nger proximal phalanx fractures Salter-Harris type II were treated. Patient records were obtained via IRB protocol and were examined retrospectively. Reduction was done via a pencil technique or a 90/90-fl exion technique.